(untitled) (Medico Legal Update, 2021)
The current study includes the detection of Aeromonas sobria isolates were obtained from total 157 samples involved the clinical samples (diarrhea samples) from patients suffering from diarrheal infections during the period from April 2017 to November 2017. at AL-Central Health Laboratory in Najaf governorate. These isolates were diagnosed by four method as (Culture method, biochemical tests, Vitek@2GN cards system and Polymerase chain reaction (PCR) technique). TheVitek@2GN cards system was the best method for diagnosis, which have led to isolate and diagnosis of 33 isolate. Multidrug resistance (MDR) of bacteria were detected by MIC testing and performed with the automated VITEK@2 GN/AST compact system. A clear variation was observed in their susceptibility to 13 antibiotics disks, these isolates of A.sobria were revealed resistance for some antibiotics such as Penicillin class Methicillin, Amoxicillin, Ampicillin, Penicillin (100%), and (91.6%) for Carbenicillin, and high rates of resistance (100%) to Cephalosporins that represented by Ceftazidime, Cefotaxime, Cefoxitin and Cefepime. The investigation of mobile genetic elements among isolates demonstrated thatA.sobria have been Class I integron genes (class 1 integron represented by integrase intI1, and IMP genes).